How to Improve Value Creation by Service Interaction: The Role of Customer–Environment Fit and Efficacy - Hong, Liang; Yu, Hongyan; Wang, Tingyi (Frontiers in Psychology, 2020)
Under the service-dominant logic, the interactions between employee and customer create opportunities for value creation. Yet research has ignored the various mechanisms service interaction might improve customer value creation. This study develops a conceptual model of customer-environment fit (C-E fit) from the perspective of customer, and conduct empirical research to examine the mediating effect of C-E fit between service interaction and customer value creation and the associated boundary conditions. With data from 435 customer questionnaires, the results show that service interaction has positive effect on value creation (utilitarian and hedonic); customer-product fit and customer-employee fit act as mediators between service interaction and value creation; customer self-efficacy moderates the mediating effects of two mediators on the relationship between service interaction and value creation; customer other-efficacy only moderates the mediating effects of customer-employee fit on the relationship between service interaction and value creation. Implications for theoretical and practical are also discussed.